HUBUNGAN ASUPAN ENERGI DAN PROTEIN DENGAN STATUS GIZI NARAPIDANA UMUM WANITA - Selvina Arum Dewanti; M. Zen Rahfiludin; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
The prisoners have the right to receive worth meal service. The food must meet the balanced nutrition in terms of both quality and quantity as well as being safe to consume in order to improve the quality of human resources. In fact, food services in prisons Women Class IIA Semarang 2016 do not meet the adequacy level of energy and protein prisoners. The purpose of this research to analyze the association of energy and protein intake with nutritional status of common women prisoners. The research method used is quantitative with cross sectional approach. Sampling technique used is total sampling amounted to 45 prisoners. data collectionis done by the submission of written informed consent, data collection on respondents’ identities, assessment of nutritional status, assessment on energy and protein intake with methods of food weighing during three days which are not consecutive, and documentation. The results showed that the average intake of energy consumed by common women prisoners amounted to 1489 kcal, the average intake of protein consumed amounted to 49.5 g, average BMI of 25.8 kg/m2 and an average of MUAC is 28.0 cm. The test results of Pearson Product Moment showed that there is a association of energy intake and nutritional status (BMI) of common women prisoners (p=0.001; r=0.483), there is a association of energy intake and nutritional status (MUAC) of common women prisoners (p=0.003; r=0.428), there is a association of protein intake with nutritional status (BMI) of common women prisoners (p=0.002; r=0.453), and there is a association of protein intake with nutritional status (MUAC) of common women prisoners (p=0.006; r=0.406).